Qualitative and Quantitative Studies of the Fish Fauna in the Drieksh Dam Lake(Tartous-Syria) - حسن محمـد; النسر أمينة; الركاد منار (Latakia University Journal -Biological Sciences Series, 2021)
This study aimed at determining the fish fauna composition in Drieksh lake. Samples were collected between May 2019 and August 2020 from three sites along the Qais River down to the Dam: ALdlbeh spring, Dam reservoir, Dam overflowing. A total of (756) individuals were collected. Our results showed the presence of five main fish species belonging to Cyprinidae family (Cyprinus carpio, , Nemachilus tigris, Cthenopharygodon idella, Gibelion catla, Acanthobrama centisguama). Tow strains of Cyprinus carpio The results also showed that the most frequent fish species was the Cyprinus carpio were found: Scaled carp and Mirro carp which recorded in all the studied sites, where the Dam was the richest site. Cyprinus carpio, Gibelion catla were spring least recorded species during the study period.